Exploring Generation Z's Influence on Tourism Industry: A Bibliometric Analysis - Anward, Ryan Juminta; Simon, Helene Elisabeth; Nurhidayati, Sri Endah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
Generation Z plays a crucial role in shaping the tourism industry, distinguished by its unique characteristics and strong digital expertise. Using bibliometric analysis, this study examined 192 publications indexed in the Scopus database between 2018 and 2024. The findings indicate an increasing interest among academics after 2020, with a focus on collaborative efforts and global contributions. Key themes include social media, sustainability, and virtual reality, reflecting evolving research directions in Generation Z's travel preferences. Based on these findings, future studies should explore longitudinal analyses and cross-cultural comparisons to refine tourism strategies, leveraging innovative technologies and marketing approaches to increase the engagement with Generation Z travellers.